Association of cardiometabolic index with all-cause and cause-specific mortality among overweight and obese adults: a cohort study - Luo, Xi; Cai, Bin; Jin, Wei-Wei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aimed to explore the associations of cardiometabolic index (CMI) with all-cause and cause-specific mortality among the overweight and obese population.MethodsMortality data for 13,674 participants with overweight or obesity were sourced from the National Death Index (NDI) and linked to the National Health and Nutrition Examination Survey (NHANES) datasets. We specifically examined the correlations of CMI with all-cause, premature, and cancer mortality. To ensure a comprehensive analysis, various statistical techniques were employed, including the Cox regression model, subgroup and sensitivity analysis, and restricted cubic spline (RCS) regression analysis. We also explored the potential mediating effect of inflammation-related indicators within these associations.ResultsAfter adjusting for all covariates, CMI remained positively associated with all-cause, premature, and cancer mortality among overweight and obese adults. For all-cause mortality, the hazard ratio (HR) was 1.14 [95% confidence interval (CI): 1.01–1.28, P = 0.041]. For premature mortality, the HR was 1.24 (95% CI: 1.08–1.42, P = 0.003). For cancer mortality, the HR was 1.33 (95% CI: 1.08–1.63, P = 0.006). When continues CMI was stratified into quartiles, significant correlations were maintained with all-cause mortality (P for trend = 0.003), premature mortality (P for trend = 0.006), and cancer mortality (P for trend = 0.007). Subgroup and sensitivity analyses indicated the robustness of results. Mediation analysis revealed that neutrophils mediated 16.27% of the correlation between CMI and all-cause mortality, and 11.01% of the association between CMI and premature mortality.ConclusionsElevated CMI is positively associated with all-cause, premature, and cancer mortality among overweight and obese adults. The associations appeared to be partially mediated by inflammatory pathways, suggesting a mechanism linking CMI to adverse health outcomes. These findings may offer valuable insights for early risk stratification and the formulation of intervention strategies within overweight and obese populations.